Potential Utilization of Kaolin from South Kalimantan as a Substitute for Import Clay in Cement Board Making - Faiza Elisa Hasfianti; I Gede Dewa Putra Prabawa; Nurhidayati Nurhidayati; Rinnie Nintasari; Nurmilatina Nurmilatina (Balai Besar Keramik, 2021)
The cement board industry in Indonesia still depends on imported materials, such as the cement board industry in South Kalimantan which still uses clay raw materials from Taiwan. Limited information on the potential use of local clay as an important clay substitution is the reason this research is needed. Identification of local clay factors was carried out by XRD, XRF, and SEM testing. The kaolin that was tested was the kaolin Tatakan and Limamar. The results of the analysis of the kaolin material were compared with the imported clay. The analysis showed that the clay used by the industry was illite with the main compound content of SiO2 (54.63%) and Al2O3 (28.23%). The results of the analysis of local clay (kaolin) tests showed that the content of compounds with imported clay was shown by kaolin placemat (SiO2 55.92%, Al2O3 29.13%), kaolin Limamar (SiO2 55.04%, Al2O3 32.71%). The quality of the application of kaolin as a substitute for imported clay in the manufacture of cement board on a laboratory scale shows the result that is not much different in the density and porosity values. The strength value of cement board with kaolin limitation gives a high enough value but it is below the standard value for PT SNI's cement board product.